Nocturnal Hypoxia in ALS Is Related to Cognitive Dysfunction and Can Occur as Clusters of Desaturations - Park, Su-Yeon (Public Library of Science, 2013)
BACKGROUND: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that leads to progressive weakness of the respiratory and limb muscles. Consequently, most patients with ALS exhibit progressive hypoventilation, which worsens during sleep. The aim of this study was to evaluate the relationship between nocturnal hypoxia and cognitive dysfunction and to assess the pattern of nocturnal hypoxia in patients with ALS. METHOD: Twenty-five patients with definite or probable ALS underwent neuropsychologic testing, nocturnal pulse oximetry, and capnography. Patients were grouped according to the presence of nocturnal hypoxia (SpO(2)<95% for ≥10% of the night) and their clinical characteristics and cognitive function were compared. RESULTS: Compared to patients without nocturnal hypoxia, those with nocturnal hypoxia (n = 10, 40%) had poor memory retention (p = 0.039) and retrieval efficiency (p = 0.045). A cluster-of-desaturation pattern was identified in 7 patients (70%) in the Hypoxia Group. CONCLUSIONS: These results suggest that nocturnal hypoxia can be related to cognitive dysfunction in ALS. In addition, a considerable number of patients with ALS may be exposed to repeated episodes of deoxygenation–reoxygenation (a cluster-of-desaturation pattern) during sleep, which could be associated with the generation of reactive oxygen species. Further studies are required to define the exact causal relationships between these phenomena, the exact manifestations of nocturnal cluster-of-desaturation patterns, and the effect of clusters of desaturation on ALS progression.